2018
DOI: 10.3389/fped.2018.00096
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Harm of Cytomegalovirus Infection in Immunocompetent Critically Ill Children

Abstract: Cytomegalovirus (CMV) is a ubiquitous infection that causes disease in congenitally infected children and immunocompromised patients. Although nearly all CMV infections remain latent and asymptomatic in immunologically normal individuals, numerous studies have found that systemic viral reactivation is common in immunocompetent critically ill adults, as measured by detection of CMV in the blood (viremia). Furthermore, CMV viremia is strongly correlated with adverse outcomes in the adult intensive care unit (ICU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 107 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…CMV infection is also connected with immune system paralysis that is characterized by enhanced IL-10 and NFkβ production, lymphopenia, reduction of IFN-γ producing T cells, and increase tissue damage by dysregulated cytokine production. Immune response during CMV infection is generated a favorable environment for secondary bacterial infections [ [27] , [28] , [29] ]. MeV infection is another example of immunosuppressive characteristics that are associated with a secondary bacterial infection.…”
Section: Mechanisms Of Viral Predisposition To Secondary Bacterial Inmentioning
confidence: 99%
“…CMV infection is also connected with immune system paralysis that is characterized by enhanced IL-10 and NFkβ production, lymphopenia, reduction of IFN-γ producing T cells, and increase tissue damage by dysregulated cytokine production. Immune response during CMV infection is generated a favorable environment for secondary bacterial infections [ [27] , [28] , [29] ]. MeV infection is another example of immunosuppressive characteristics that are associated with a secondary bacterial infection.…”
Section: Mechanisms Of Viral Predisposition To Secondary Bacterial Inmentioning
confidence: 99%
“…Furthermore, more studies found that CMV reactivation was prevalent in immunocompetent critically ill patients with a high incidence of 15–20%. Worse still, CMV reactivation was also considered to be correlated with clinical adverse outcomes and the increase of inpatient mortality ( Limaye et al, 2008 ; Papazian et al, 2016 ; Alyazidi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, CMV remains a burden to human health. This is particularly true for vulnerable groups such as children with congenital CMV infection (12), and "frail" patients suffering from autoimmune disease-even if they are otherwise immunocompetent (12,13).…”
Section: Introductionmentioning
confidence: 99%